Flame Retardancy Effects of Graphene Nanoplatelet/Carbon Nanotube Hybrid Membranes on Carbon Fiber Reinforced Epoxy Composites. (9th July 2013) - Zhuo, Dongxian; Wang, Rui; Wu, Lixin; Guo, Yanhua; Ma, Lin; Weng, Zixiang; Qi, Jinyu
Abstract : Carbon nanotube/graphene nanoplatelet (MWCNT/GNP) hybrid membranes with lower liquid permeability and better barrier effect compared to MWCNT membranes were successfully synthesized by vacuum filtering. Their morphologies, water permeability, and pore structures were characterized by a scanning electron microscope (SEM) and nitrogen adsorption isotherms. Furthermore, MWCNT/GNP membranes were used to improve the flame retardancy of carbon fiber reinforced polymer (CFRP) composites, and the influence of weight percentage of GNPs on the permeability and flame retardancy of MWCNT/GNP membranes was systematically investigated. Results show that incorporation of MWCNT/GNP membranes on CFRP composite plates can remarkably improve the flame retardancy of CFRP composites. Specifically, the incorporation of hierarchical MWCNT/GNP membrane with 7.5 wt% of GNP displays a 35% reduction in the peak heat release rate (PHRR) for a CFRP composite plate with the epoxy as matrix and a 11% reduction in PHRR compared with the incorporation of MWCNT membrane only. A synergistic flame retarding mechanism is suggested to be attributed to these results, which includes controlling the pore size and penetrative network structure.